Jangka Waktu Penyelesaian Kewajiban Perkara Penundaan Pembayaran Utang Di Pengadilan Niaga (Studi Putusan Nomor 134/Pdt.Sus-PKPU/2023/PN.Niaga.Jkt.Pst: The Period Of Settlement Of Posponement Of Debt Payment Obligations Cases In The Commercial Court (Study Of Decision Number 134/Pdt.Sus-PKPU/2023/Pn.Niaga.Jkt.Pst.) - Rachel Zalfaa Hermawan; Asep Iwan Iriawan (Faculty of Law, Universitas Trisakti, 2025)
The Commercial Court in proceedings related to the time to grant a request for postponement of debt payment obligations (PKPU) when submitted by Creditors in accordance with Article 225 Paragraph (3) must be decided within 20 days, but in Decision number 134/Pdt.Sus-PKPU/2023/PN.Niaga.Jkt.Pst which was registered with the registrar of the Commercial Court on April 17, 2023 it was only decided for 60 days, namely on July 3, 2023. The problem is whether the PKPU period in decision number 134/Pdt.Sus-PKPU/2023/PN.Niaga.Jkt.Pst. In accordance with the provisions of the legislation and the legal consequences of the decision that was decided to exceed the time period, this research uses normative law. The results of this analysis are that the decision on the application for a PKPU statement must be decided within 20 days of registration, the decision exceeds the time period, there are omissions and discrepancies between the regulations and implementation between the Bankruptcy and PKPU Law and the judge's decision in Decision No.134/Pdt.Sus-PKPU/2023/PN.Niaga.Jkt.Pst. as a result, it causes losses and legal uncertainty. Solution In the future, the panel of judges will pay more attention to and uphold legal certainty and it is necessary to regulate the provisions of sanctions or consequences if the decision exceeds the time period in the Bankruptcy and PKPU Law.